After the end of history conversations with Francis Fukuyama - Fukuyama, Francis (Washington Georgetown University Press, 2021)
Francis Fukuyama is one of the most significant political theorists of the past thirty years. Bursting into public awareness in 1989 with his provocative thesis about "the end of history," Fukuyama has made fascinating contributions to a wide range of subjects - the importance of trust in societies, the potential dangers of biotechnology, the development of political authority and the modern state, and most recently, the role of identity in politics. This book records a series of conversations with Fukuyama in which he discusses his background and its role in shaping his thinking, the context and genesis of his major works, and his thoughts in light of the dramatic developments of the past decade, especially the rise of populism around the world. The result is a fascinating picture of a major intellectual. The book both provides an overview of Fukuyama's thought and reveals new insights into his best-known work. This book also allows readers to trace the themes which have animated Fukuyama's entire intellectual career
Includes bibliographical references and index.
Keywords: Fukuyama, Francis--Interviews.